2003
DOI: 10.1002/ab.10034
|View full text |Cite
|
Sign up to set email alerts
|

Variability in behavior frequencies and consistency in transactions across seasons in captive Japanese macaques (Macaca fuscata)

Abstract: Consistent interspecific differences are found in macaque species, ranging from highly hierarchical and nepotistic societies to more tolerant and open social organizations. It still remains to be demonstrated whether intraspecific variation is narrower than interspecific variation. Herein, we quantified social behavior in a captive group of Japanese macaques (Macaca fuscata) to estimate the range of intraspecific variation for a full array of measurements in three different seasons. Despite an increased freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Our findings differ from at least one previous account by Ruehlmann et al (1988) who report increased wounding rates in the birthing season for captive seasonal breeders such as rhesus macaques. However, behavioral data from wild Japanese macaques is consistent with the seasonal patterns of wounding reported here; it is well established that aggressive behaviors by Japanese macaques peak during the mating season, especially aggression by males (Abegg, Petit, & Theirry, 2003; Eaton, Modahl, & Johnson, 1981; Jack, 2012). Wilson and Boelkins (1970) reported that free‐ranging rhesus macaque males (but not females) were wounded and died more frequently during the mating season compared to any other time of the year.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings differ from at least one previous account by Ruehlmann et al (1988) who report increased wounding rates in the birthing season for captive seasonal breeders such as rhesus macaques. However, behavioral data from wild Japanese macaques is consistent with the seasonal patterns of wounding reported here; it is well established that aggressive behaviors by Japanese macaques peak during the mating season, especially aggression by males (Abegg, Petit, & Theirry, 2003; Eaton, Modahl, & Johnson, 1981; Jack, 2012). Wilson and Boelkins (1970) reported that free‐ranging rhesus macaque males (but not females) were wounded and died more frequently during the mating season compared to any other time of the year.…”
Section: Discussionsupporting
confidence: 88%
“…Social styles appear to be fairly stable within each species, provided that studies compare the same categories of individuals, using the same variables measured with standardized methods under similar conditions. Living conditions, population density, and reproductive seasonality have been shown to have limited effects on well‐documented traits such as intensity of aggression, rates of counter‐aggression, and rates of reconciliation (Abegg et al, 2003; Aureli, 1992; Balasubramaniam et al, 2012; Colmenares, 2006; Demaria & Thierry, 1989; Judge & de Waal, 1997; Majolo & Koyama, 2006; Schino et al, 1998). The magnitude of variation appears to be significantly smaller within species than between species (Balasubramaniam et al, 2012; Butovskaya & Kozintsev, 1996; Castles et al, 1996; Duboscq et al, 2013; Rebout et al, 2020; Sueur et al, 2011; Thierry et al, 2008; Tyrrell et al, 2020).…”
Section: Covariation As a Patternmentioning
confidence: 99%
“…Before animal FACS were developed, Kanazawa [ 47 ] noted that FACS was the most standardised tool for human facial expressions, but without knowing how FACS could be translated to macaques, the author not only questioned previous results investigating facial expressions, but also stated that it was very difficult to identify critical facial movements. This might be why studies of Japanese macaque behaviour usually have very few facial behaviours included [ 48 50 ] even though face-to-face engagement is important in Japanese macaque social interactions [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%